A rapid and simple one-step F-18 labeling of peptides - Jacobson, Orit (2011)
OBJECTIVES: Labeling biomolecules with (18)F is usually done through coupling with prosthetic groups, which requires several time-consuming radiosynthesis steps and therefore results in low labeling yield. In this study we designed a simple one-step (18)F-labeling strategy to replace the conventional complex and long process of multiple-step radiolabeling procedure. METHODS: Both Monomeric and dimeric cyclic RGD peptides were modified to contain 4-NO(2)-3-CF(3) arene as precursors for direct (18)F labeling. Binding of the two functionalized peptides to integrin α(v)β(3) was tested in vitro using MDA-MB-435 human breast cell line. The most promising functionalized peptide, the dimeric cyclic RGD, was further evaluated in vivo in an orthotopic MDA-MB-435 tumor xenograft model. RESULTS: The use of relatively low amount of precursor (~0.5μmol), gave reasonable yield, ranging from 7–23% (decay corrected, calculated from start of synthesis) after HPLC purification. Overall reaction time was 40 min and the specific activity of the labeled peptide was high. Modification of RGD peptides did not significantly change the biological binding affinities of the modified peptides. Small animal PET and biodistribution studies revealed integrin specific tumor uptake and favorable biokinetics. CONCLUSIONS: We have developed a novel one-step (18)F radiolabeling strategy for peptides that contain a specific arene group, which shortens reaction time and labor significantly, requires low amount of precursor and results in specific activity of 79 ± 13 GBq/μmol. Successful introduction of 4-fluoro-3-trifluoromethylbenzamide into RGD peptides may be a general strategy applicable to other biologically active peptides and proteins.